Adabiy va sheriy tarjimalarning xususiyati - Atashova, F.D (SCIENCE and SOCIETY, 2025)
The article discusses literary translation. In general, it can be said that it faces the same tasks as other types of transla- tion. It is important to note that literary translation is a foreign cultural likeness of the original literary text that meets the literary and communicative requirements and ideas of society at a certain historical stage. It can be said that literary translation is a special genre of literature with certain structural, content, and emotional-evaluative properties. In literary translation, separate subtypes of translation are distinguished depending on whether the original belongs to the genre of fiction. Such subtypes include translation of poetry, translation of plays, translation of fiction, translation of song lyrics, etc.
Keywords: literary translation; written or oral text; poetic translation; linguistic categories; analysis and synthesis of the translation process